The last billion years a geological history of the Maritime Provinces of Canada - Fensome, Robert 1951-; Williams, Graham L. (Nimbus Publishing, 2022)
Expanded and updated edition of bestselling full-colour history of geological heritage in Nova Scotia, New Brunswick, and PEI, featuring texts from experts and thousands of illustrations, including paintings, photographs, maps, and diagrams. The rocks and fossils of the Maritime Provinces of Canada (New Brunswick, Nova Scotia, and Prince Edward Island) tell a fascinating story of the last billion years. The story unravels many surprises, for example: - Halifax and southern Nova Scotia were once situated near the South Pole and attached to Africa. - The positions of present-day Halifax and Saint John were once on separate continents. - The red rocks of Prince Edward Island were formed in a monsoonal climate. - Cliffs around the Bay of Fundy have yielded the oldest dinosaurs in Canada. - As recently as 20,000 years thick ice covered the Maritimes and extended onto the continental shelf. These topics, and many more, are explored in this revised and updated edition of The Last Billion Years, a book for anyone interested in the origin and evolution of the Maritime Provinces. Beautifully and profusely illustrated in full colour, The Last Billion Years features original paintings of ancient vistas, photographs, and informative diagrams and sketches.
Keywords: Historische Geologie; Geologie; Maritime Provinzen; Nova Scotia; Kanada; New Brunswick; Prince Edward Island; Geology / Maritime Provinces; Historical geology / Maritime Provinces; Geology; Historical geology; Maritime Provinces